1975
DOI: 10.1111/j.1469-8986.1975.tb01298.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Stress Films on Dream Affect and on Respiration and Eye‐Movement Activity During Rapid‐Eye‐Movement Sleep

Abstract: The effects of stress on the affective content of dreams and on rapid‐eye‐movement (REM) period eye‐movement activity and respiration were studied. The experiment was also designed to examine the similarity between walking and sleeping states in the respiratory correlates of emotion. Sleep records and dream reports were collected following the viewing of stress and neutral films. The stress films significantly increased dream anxiety and also increased REM‐period respiratory irregularity among those Ss who, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
2

Year Published

1979
1979
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 22 publications
1
40
2
Order By: Relevance
“…With this background, it is tempting to relate the particular benefit for emotional memory from late retention sleep to enhanced amygdalar activity accompanying the extended REM sleep epochs of this period. This conclusion is also supported by several other studies in animals and humans suggesting that patterns of emotional arousal induced during learning become reactivated during REM sleep, thereby strengthening memory traces and connectivity within respective neural networks (Goodenough et al 1975;Hennevin et al 1998;Maho and Hennevin 1999). In the case of emotional declarative memories, this influence could be mediated via modulatory influences of the amygdala on the hippocampal memory system Hamann et al 1999;Roozendaal 2000).…”
Section: Emotional Memory and Rem Sleepsupporting
confidence: 76%
“…With this background, it is tempting to relate the particular benefit for emotional memory from late retention sleep to enhanced amygdalar activity accompanying the extended REM sleep epochs of this period. This conclusion is also supported by several other studies in animals and humans suggesting that patterns of emotional arousal induced during learning become reactivated during REM sleep, thereby strengthening memory traces and connectivity within respective neural networks (Goodenough et al 1975;Hennevin et al 1998;Maho and Hennevin 1999). In the case of emotional declarative memories, this influence could be mediated via modulatory influences of the amygdala on the hippocampal memory system Hamann et al 1999;Roozendaal 2000).…”
Section: Emotional Memory and Rem Sleepsupporting
confidence: 76%
“…44,46 Other studies note more global changes to include increased sleep latency, sleep fragmentation, nocturnal awakenings, and periodic limb movements. 41,43,45,46 The most consistent PSG finding is an increase in overnight awakenings. 49,50 Interestingly, when comparing PSG variables in patients with NDO versus TRN, those with TRN had improved SE, decreased WASO, and increased stage N3 sleep.…”
Section: Discussionmentioning
confidence: 92%
“…There are a number of small studies that have reported variable PSG characteristics in nightmare sufferers. [43][44][45][46][47][48][49] REM-specific abnormalities to include absence of early REM periods, increased REM sleep latency, and increased REM periods, as well as NREM changes to include reduced slow wave sleep, have been reported. 44,46 Other studies note more global changes to include increased sleep latency, sleep fragmentation, nocturnal awakenings, and periodic limb movements.…”
Section: Discussionmentioning
confidence: 99%
“…Since Agnew, Webb, and Williams (1966) reported and defined the first-night effect, several researchers have described its association with reduced TST, poor SE, less REM sleep, increased SL, and increased WASO (Aber et al, 1989;Curcio, Ferrara, Piergianni, Fratello, & De Gennaro, 2004;Le Bon et al, 2000;Li et al, 2004;Scholle et al, 2003;Toussaint et al, 1997 Acute experimental psychological stress in healthy participants had a consistent effect on REM sleep in early studies. In the 1960s and 1970s, many researchers reported that presleep stimulation influenced REM activity and awakenings (Baekeland, Koulack, & Lasky, 1968;Cluydts & Visser, 1980;Cohen, 1975;Goodenough, Witkin, Koulack, & Cohen, 1975). Pre-sleep stress, such as an aversive film (Baekeland et al, 1968;Cluydts & Visser, 1980;Goodenough et al, 1975;Lauer, Riemann, Lund, & Berger, 1987) or impersonal treatment (Cohen, 1975), was associated with increased frequency of rapid eye movements (REM density; Goodenough et al, 1975;Lauer et al, 1987), number of awakenings (Baekeland et al, 1968;Cluydts & Visser, 1980), and longer SL (Goodenough et al, 1975).…”
Section: Experimental Stress On Sleepmentioning
confidence: 99%
“…In the 1960s and 1970s, many researchers reported that presleep stimulation influenced REM activity and awakenings (Baekeland, Koulack, & Lasky, 1968;Cluydts & Visser, 1980;Cohen, 1975;Goodenough, Witkin, Koulack, & Cohen, 1975). Pre-sleep stress, such as an aversive film (Baekeland et al, 1968;Cluydts & Visser, 1980;Goodenough et al, 1975;Lauer, Riemann, Lund, & Berger, 1987) or impersonal treatment (Cohen, 1975), was associated with increased frequency of rapid eye movements (REM density; Goodenough et al, 1975;Lauer et al, 1987), number of awakenings (Baekeland et al, 1968;Cluydts & Visser, 1980), and longer SL (Goodenough et al, 1975).More recently, Koulack, Prevost, and De Koninck (1985) gave an intellectually challenging test to 16 male university students; the suggestion of inferiority led to longer SL and lower REM density than at baseline. Germain, Buysse, Ombao, Kupfer, and Hall (2003) reported that acute experimental psychological stress reduced rapid eye movement counts during the last REM sleep period in healthy participants when compared to non-stressed control participants.…”
mentioning
confidence: 99%